2021
DOI: 10.3390/ijerph18042124
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Degradation of Carbon Tetrachloride by Microscale Ag/Fe Bimetallic Particles

Abstract: Cost-effective zero valent iron (ZVI)-based bimetallic particles are a novel and promising technology for contaminant removal. The objective of this study was to evaluate the effectiveness of CCl4 removal from aqueous solution using microscale Ag/Fe bimetallic particles which were prepared by depositing Ag on millimeter-scale sponge ZVI particles. Kinetics of CCl4 degradation, the effect of Ag loading, the Ag/Fe dosage, initial solution pH, and humic acid on degradation efficiency were investigated. Ag deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…As shown in Table 1, the degradation reactions of ZVI in halogenated hydrocarbons were all fitted with pseudo-first-order reaction kinetics [33,34]. The value of K obs in the kinetic equation represents the apparent degradation rate; the higher the value of K obs , the higher the degradation efficiency.…”
Section: Kinetic Analysis Of Tce Degradation With Different Ni Conten...mentioning
confidence: 99%
“…As shown in Table 1, the degradation reactions of ZVI in halogenated hydrocarbons were all fitted with pseudo-first-order reaction kinetics [33,34]. The value of K obs in the kinetic equation represents the apparent degradation rate; the higher the value of K obs , the higher the degradation efficiency.…”
Section: Kinetic Analysis Of Tce Degradation With Different Ni Conten...mentioning
confidence: 99%
“…A recent study reported that AgNP morphology may change from a dispersed 18 spherical shape to larger aggregates owing to the release of Ag + possibly because of (i) the nano bridges created by adsorption and/or redox conversion of Ag + into Ag 0 at the particle surface to connect nearby particles, and (ii) the growth of reformed small AgNPs around old AgNPs (Yu et al, 2014). Other reports showed that Ag + released from AgNPs and possible electron transfer from Fe 0 to Ag + could form a galvanic couple, which may accelerate NZVI-water corrosion (Zhuang et al, 2011;Zhu et al, 2021). Therefore, interactions of Ag + ions (E0 Ag/Ag + 0.799 V) with NZVI (E0 Fe/Fe 2+ 0.44 V) and AgNPs through adsorption and/or electron transfer processes may alter the particle aggregation behavior and surface reactivity.…”
Section: Heteroaggregation and Homoaggregation Of Agnpsmentioning
confidence: 99%
“…Numerous studies have addressed different routes for the disposal of carbon tetrachloride by multiple means, which are not only chemical but also physical, such as pyrolysis [5][6][7][8][9]. However, its disposal through recycling it into a useful product for the chemical industry has hardly been addressed.…”
Section: Introductionmentioning
confidence: 99%